Modeling the effects of Crisis Intervention Team (CIT) training for police officers: How knowledge, attitudes, and self-efficacy drive de-escalation skills and referral decisions. (July 2022) - Compton, Michael T.; Krishan, Shaily; Broussard, Beth; Bakeman, Roger; Fleischmann, Matthew H.; Hankerson-Dyson, Dana; Husbands, Letheshia; Stewart, Tarianna; D'Orio, Barbara; Watson, Amy C.
Abstract: Objective: Prior research on Crisis Intervention Team (CIT) training for police officers has demonstrated improvements in knowledge, attitudes, self-efficacy, and stigma, but how these factors work together to influence behavioral outcomes like de-escalation skills and referral decisions remains unstudied. Method: 251 CIT-trained and 335 non-CIT officers completed in-depth surveys measuring these six constructs. We used structural equation modeling to test fit of the data to our hypothesized model and made indicated changes to improve fit. Results: An alternate 8-path model (with three paths originally hypothesized being removed) fit reasonably well, and allowing path coefficients to differ for CIT and non-CIT groups resulted in models with similar fit statistics. Conclusion: CIT training enhances knowledge and attitudes, both of which have beneficial effects on stigma. Though an important outcome itself, lower stigma does not have an effect on de-escalation skills and referral decisions, though self-efficacy clearly does.